Effect of loading methods on the performance of hierarchical porous carbon/sulfur composites in lithium sulfur batteries. (20th August 2021) - Zhang, Bo; Guo, Zhijie; Zhao, Yingming; Luo, Birong; Li, Dejun; Zhao, Teng; Sure, Jagadeesh; Vishnu, Sri Maha; Abdelkader, Amr; Harris, Chris; Xi, Kai
Abstract: Lithium-sulfur batteries have shown increasing promise for high energy densities and reduced costs. Facile sulfur loading techniques demonstrate a critical way to achieving high dispersions of sulfur in the host's matrix, improving conductivity and simultaneously decreasing the active mass loss from the cathode. Here we investigate the effect of sulfur loading methods on the electrochemical performance of porous carbon/sulfur composites containing approximately 70 wt% sulfur. Three different loading techniques are tested, including one-step molten sulfur impregnation (155°C), two-step molten sulfur impregnation (155°C + 300°C) and a sulfur organic solution impregnation, in which the entire microporous volume of carbon is filled by sulfur. It is found that the simple sulfur organic solution impregnation method is the most effective in enhancing the electrochemical performance of the hierarchical porous carbon/sulfur composite cathode in the lithium-sulfur battery system, due to the weaker interaction occurring between the sulfur and microporous carbon. Our work demonstrates the impact of sulfur loading method on the electrochemical performance of lithium-sulfur batteries, which offers new insights into the preparation technology of electrodes.